Better Informing the Market? The Teaching Excellence Framework (TEF) - Shattock, Michael (International Higher Education, 2018)
The current British policy toward higher education emphasizes that market forces and competition represent key factors in raising quality. Intense competition already exists in research through the Research Excellence Framework (REF) but this, it is argued, has led to a diversion of interest away from teaching. The REF is therefore to be paralleled by a Teaching Excellence Framework (TEF), which will better inform the student market. The TEF, the first results of which were announced in June, is metrics based and categorizes teaching as qualifying for a Gold, Silver, or Bronze award. The metrics have been heavily criticized. The article describes the metrics involved and the reactions to the first round of TEF awards.